Kandungan Informasi atas Peristiwa Stock Split - Suntoro, Denny; Subekti, Imam (TEMA, 2003)
The objective of this study is to investigate the market reaction associated with stock split event. Abnormal return and trading volume activity are proxies of market reaction. And, return change is used a proxy of stock split event. Event study technique is used for this observation with abnormal return and trading volume activity as dependent variable, and return changes as independent variable. Sample used in this study are stock split event in The Jakarta Stock Exchange (JSX) for year 2000 up to 2002. Samples are selected by purposive sampling method. The result showed that association between abnormal return, trading volume activity and stock split event was significant. The examination result for abnormal return showed that market reaction was done on d-2 and d+1 (d = announcement day)positively, and on d+4 negatively. For trading volume activity, the examination result showed that market reaction was done d+2 and d+5 negatively. So, stock split can make investors would do well to look at the information behind stock split to take decision. This has proven that there is a market reaction on surrounding stock split announcement period. Key words; stock split, abnormal return, trading volume activity, return change.